(y+9)(y+9)=144

Simple and best practice solution for (y+9)(y+9)=144 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (y+9)(y+9)=144 equation:


Simplifying
(y + 9)(y + 9) = 144

Reorder the terms:
(9 + y)(y + 9) = 144

Reorder the terms:
(9 + y)(9 + y) = 144

Multiply (9 + y) * (9 + y)
(9(9 + y) + y(9 + y)) = 144
((9 * 9 + y * 9) + y(9 + y)) = 144
((81 + 9y) + y(9 + y)) = 144
(81 + 9y + (9 * y + y * y)) = 144
(81 + 9y + (9y + y2)) = 144

Combine like terms: 9y + 9y = 18y
(81 + 18y + y2) = 144

Solving
81 + 18y + y2 = 144

Solving for variable 'y'.

Reorder the terms:
81 + -144 + 18y + y2 = 144 + -144

Combine like terms: 81 + -144 = -63
-63 + 18y + y2 = 144 + -144

Combine like terms: 144 + -144 = 0
-63 + 18y + y2 = 0

Factor a trinomial.
(-21 + -1y)(3 + -1y) = 0

Subproblem 1

Set the factor '(-21 + -1y)' equal to zero and attempt to solve: Simplifying -21 + -1y = 0 Solving -21 + -1y = 0 Move all terms containing y to the left, all other terms to the right. Add '21' to each side of the equation. -21 + 21 + -1y = 0 + 21 Combine like terms: -21 + 21 = 0 0 + -1y = 0 + 21 -1y = 0 + 21 Combine like terms: 0 + 21 = 21 -1y = 21 Divide each side by '-1'. y = -21 Simplifying y = -21

Subproblem 2

Set the factor '(3 + -1y)' equal to zero and attempt to solve: Simplifying 3 + -1y = 0 Solving 3 + -1y = 0 Move all terms containing y to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1y = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1y = 0 + -3 -1y = 0 + -3 Combine like terms: 0 + -3 = -3 -1y = -3 Divide each side by '-1'. y = 3 Simplifying y = 3

Solution

y = {-21, 3}

See similar equations:

| x-25x/100=617.05 | | 2x^2-3=-4 | | 3[2x+8]=5[-8x-6] | | 0=2x^2-13x+11 | | 8[x+5]=5 | | 17=x/3+10 | | 2x+5=(((3x-5)*8/7)+65-98)*23/46+78-53 | | w/9+15=18 | | 21x^3+x^2-5x-1=0 | | m/4-2=6 | | 15y-12=33 | | 16=5r-14 | | 32=3c+8 | | f(x)=3x^2-7x+2 | | 5x+8+7=3x-6-8 | | (4b-3)(4b-3)=169 | | x-2.9=9.1 | | 7x/2-3/2-4/1=5x+1/3 | | (a-5)(a-5)=196 | | 1045.95-1045.95x/100=617.05 | | 0=25x^2-70x+13 | | x-3.9=4.1 | | 25x^2-70x+13=0 | | x^4-1.36x^2+1=0.909 | | 1045.95-x/100=617.05 | | 25x^2-70+13=0 | | 2l-18=36 | | 2n+1=56 | | 8x+y=198 | | (2x-7)(x^2-9)(2x-5)-91=0 | | 5x+8y=198 | | 20x/100=516.06 |

Equations solver categories